Accessibility of Health Care Services for People with Disabilities: Case of Lithuania - Dromantienė, Leta; Baranauskienė, Ingrida (Social Welfare: Interdisciplinary Approach, 2025)
The paper examines the legal regulation of patients’ rights to quality healthcare in Lithuania and the accessibility of healthcare services for people with disabilities. As the number of people with disabilities in Lithuania is very high as every tenth inhabitant has disability, we can state that people with disabilities can be considered as a health disparity population, underrepresented and unseen in mainstream research studies on health care. The paper applies accessible research design that means that people with disabilities can fully participate in research on accessibility of health care services and contribute to advances in the health care system. Applied research methods – content analysis of legal regulation on patient rights and health services; state reports, other national and international documents; conducted ethnographic study and analysis of attitudes of people with disabilities, their relatives and specialists towards accessibility of health care services according different dimensions of accessibility – allowed to identify the barriers of access to health care services. The research brought to conclusion that the health care system in Lithuania needs changes; accessibility of health care services for people with disabilities is insufficient due to underfunding of the health care system, services are still not patient-oriented and do not meet their needs, obvious problems of discrimination and ethics; limited physical availability of health care services for people with disabilities; other problems also were identified. Knowing their needs will contribute to promote the accessibility of health services, avoid barriers to health care, improve the health of population in Lithuania, reduce disparities of health status, achieve social sustainability.